Approaches to Address Premature Death of Patients When Assessing Patterns of Use of Health Care Services After an Index Event. Issue 7 (July 2018) - Bush, Montika; Simpson, Ross J.; Kucharska-Newton, Anna; Fang, Gang; Stürmer, Til; Brookhart, M. Alan
Abstract : Background: Studies of the use of health care after the onset of disease are important for assessing quality of care, treatment disparities, and guideline compliance. Cohort definition and analysis method are important considerations for the generalizability and validity of study results. We compared different approaches for cohort definition (restriction by survival time vs. comorbidity score) and analysis method [Kaplan-Meier (KM) vs. competing risk] when assessing patterns of guideline adoption in elderly patients. Methods: Medicare beneficiaries aged 65–95 years old who had an acute myocardial infarction (AMI) in 2008 were eligible for this study. Beneficiaries with substantial frailty or an AMI in the prior year were excluded. We compared KM with competing risk estimates of guideline adoption during the first year post-AMI. Results: At 1-year post-AMI, 14.2% [95% confidence interval (CI), 14.0%–14.5%) of beneficiaries overall initiated cardiac rehabilitation when using competing risk analysis and 15.1% (95% CI, 14.8%–15.3%) from the KM analysis. Guideline medication adoption was estimated as 52.3% (95% CI, 52.0%–52.7%) and 53.4% (95% CI, 53.1%–53.8%) for competing risk and KM methods, respectively. Mortality was 17.0% (95%CI, 16.8%–17.3%) at 1 year post-AMI. The difference in cardiac rehabilitation initiation at 1-year post-AMI from the overall population was 0.1%, 1.7%, and 1.9% compared with 30-day survivor, 1-year survivor, and comorbidity-score restricted populations, respectively. Conclusions: In this study, the KM method consistently overestimated the competing risk method. Competing risk approaches avoid unrealistic mortality assumptions and lead to interpretations of estimates that are more meaningful. Abstract : Supplemental Digital Content is available in the text.